2016
DOI: 10.3109/10826084.2016.1160123
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Among Experience of Regret, Delay Discounting, and Worries About Future Effects of Smoking Among Current Smokers

Abstract: Background Smoking regret differs by smoker characteristics (dependence) and may be linked to delay discounting (DD), where smaller immediate rewards are preferred to larger delayed rewards. It is hypothesized that those who exhibit stronger tendencies to delay rewards also express fewer future health concerns and possibly less regret about smoking. Objectives The objective is to determine the interrelationships of regret, dependence, and delay discounting among current smokers. Methods In July 2010, 1062 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Consistent with previous research [ 5 , 13 , 33 ], the prevalence of regret was high among smokers in this study; across studies, reported regret ranges from 79% to 92% (Malaysia (79%), the United Kingdom (89%), Australia (90%), Thailand (92%), and Canada (92%)). Fong et al reported that, among United States smokers, the prevalence of smoker regret was 91% in 2004, whereas a study by O’Connor using 2010 U.S. data reported 85% regret among a similar sample of U.S. adults.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous research [ 5 , 13 , 33 ], the prevalence of regret was high among smokers in this study; across studies, reported regret ranges from 79% to 92% (Malaysia (79%), the United Kingdom (89%), Australia (90%), Thailand (92%), and Canada (92%)). Fong et al reported that, among United States smokers, the prevalence of smoker regret was 91% in 2004, whereas a study by O’Connor using 2010 U.S. data reported 85% regret among a similar sample of U.S. adults.…”
Section: Discussionsupporting
confidence: 92%
“…The findings indicate that the vast majority of smokers regret having started smoking [5,13,33]. Perceiving health risks from smoking was associated with having regret.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 40 45 O’Connor and colleagues recently explored the relationships between smokers’ feelings of regret and other characteristics such as delay discounting and worries about future health. 48 They reported that among US adult smokers completing a 2010 web-based survey, 84.4% expressed regret and that regret was positively associated with worries about the negative impact of their smoking on health, quality of life and how much they spend on cigarettes. 48 Finally, we recently reported that in 2014, 71.5% of US adult smokers expressed regret and that older and non-Hispanic white smokers were most likely to report regret.…”
Section: Introductionmentioning
confidence: 99%